Construction of a new chromosome-scale, long-read reference genome assembly for the Syrian hamster, Mesocricetus auratus. (28th May 2022) - Harris, R Alan; Raveendran, Muthuswamy; Lyfoung, Dustin T; Sedlazeck, Fritz J; Mahmoud, Medhat; Prall, Trent M; Karl, Julie A; Doddapaneni, Harshavardhan; Meng, Qingchang; Han, Yi; Muzny, Donna; Wiseman, Roger W; et al.
Abstract: Background: The Syrian hamster ( Mesocricetus auratus ) has been suggested as a useful mammalian model for a variety of diseases and infections, including infection with respiratory viruses such as SARS-CoV-2. The MesAur1.0 genome assembly was generated in 2013 using whole-genome shotgun sequencing with short-read sequence data. Current more advanced sequencing technologies and assembly methods now permit the generation of near-complete genome assemblies with higher quality and greater continuity. Findings: Here, we report an improved assembly of the M. auratus genome (BCM_Maur_2.0) using Oxford Nanopore Technologies long-read sequencing to produce a chromosome-scale assembly. The total length of the new assembly is 2.46 Gb, similar to the 2.50-Gb length of a previous assembly of this genome, MesAur1.0. BCM_Maur_2.0 exhibits significantly improved continuity, with a scaffold N50 that is 6.7 times greater than MesAur1.0. Furthermore, 21, 616 protein-coding genes and 10, 459 noncoding genes are annotated in BCM_Maur_2.0 compared to 20, 495 protein-coding genes and 4, 168 noncoding genes in MesAur1.0. This new assembly also improves the unresolved regions as measured by nucleotide ambiguities, where ∼17.11% of bases in MesAur1.0 were unresolved compared to BCM_Maur_2.0, in which the number of unresolved bases is reduced to 3.00%. Conclusions: Access to a more complete reference genome with improved accuracy and continuity will facilitate more detailed, comprehensive, and meaningful research results for a wide variety of future studies using Syrian hamsters as models.